Contributions of interfaces on the mechanical behavior of 3D printed continuous fiber reinforced composites. (18th July 2022) - Li, Shixian; Wang, Kui; Zhu, Wanying; Peng, Yong; Ahzi, Said; Chinesta, Francisco
Highlights: Effects of raster orientations and stacking sequences on the mechanical properties of printed continuous fiber filled composite were investigated. Deformation and failure mechanisms of continuous fiber reinforced composites were studied at multi-scales. Interfacial behaviors of the printed composites were studied. A novel analytical model considering interface contribution was developed. Abstract: 3D printing using continuous fiber reinforcement provides a new technical method for preparing complex components with high mechanical behaviors. However, these printed composites have great differences in interfacial behaviors, affecting overall performance. This study aimed to investigate the tensile behaviors of 3D printed continuous fiber filled composites. The structural evolutions and failure features of the composites induced by strain were analyzed with the consideration of interfaces, influenced by the reinforcement fibers, stacking sequences as well as raster orientations. A roller peeling test was conducted to quantify the interfacial strength of different materials. An analytical approach was proposed to predict the stiffness behavior of the printed composites by introducing an interfacial strengthening coefficient into the volume average stiffness model. The predictions of stiffness, for the 3D printed continuous fiber filled composites with different fibers, stacking sequences and raster orientations, were in good agreement with experimental results.